Shelter-housed cats show no evidence of faecal shedding of canine parvovirus DNA. (September 2018) - Byrne, P.; Beatty, J.A.; Šlapeta, J.; Corley, S.W.; Lyons, R.E.; McMichael, L.; Kyaw-Tanner, M.T.; Dung, P.T.; Decaro, N.; Meers, J.; Barrs, V.R.
Highlights: Faecal shedding of Carnivore protoparvovirus 1 was investigated in shelter cats. Feline faecal samples ( n = 218) were collected from three mixed cat/dog shelters in Australia. Testing for feline and canine parvoviruses (FPV, CPV) was performed using cPCR. FPV was detected in 1.8% samples and CPV was not detected in any sample. There was no evidence in this study that cats had a role as CPV reservoirs. Abstract: Canine parvovirus (CPV) and feline panleukopenia virus (FPV) are deoxyriboncucleic acid (DNA) viruses in the taxon Carnivore protoparvovirus 1 . Exposure of cats to either CPV or FPV results in productive infection and faecal shedding of virus. Asymptomatic shedding of CPVs by one-third of shelter-housed cats in a UK study suggests that cats may be an important reservoir for parvoviral disease in dogs. The aim of this cross-sectional study was to determine the prevalence of faecal shedding of CPVs in asymptomatic shelter-housed cats in Australia. Faecal samples ( n = 218) were collected from cats housed in three shelters receiving both cats and dogs, in Queensland and NSW. Molecular testing for Carnivore protoparvovirus 1 DNA was performed by polymerase chain reaction (PCR) amplification followed by DNA sequencing of the VP2 region to differentiate CPV from FPV. Carnivore protoparvovirus 1 DNA was detected in only four (1.8%, 95% confidence interval 0.49–4.53%) faecal samples from a single shelter. Sequencing identified all four positive samples as FPV. Faecal shedding of CPV by shelter-cats was not detected in this study. While the potential for cross-species transmission of CPV between cats and dogs is high, this study found no evidence of a role for cats in maintaining CPV in cat and dog populations through faecal shedding in the regions tested.